FINANCIAL PERFORMANCE OF SHARIA BANKS BEFORE AND AFTER SPIN-OFF - Prima Naomi (Journal of Innovation in Business and Economics, 2017)
This research aimed at identifying whether Bank Umum Syariah (BUS), as the result of spin-off of Unit Usaha Syariah  (UUS), has better performance compared to the period when they were still in the form of UUS. There are 4 out of 5 BUSes as a result of spin-off us as samples. The results indicate that: 1) the spin-off of UUS to become BUS has successfully increased the market share of each BUS; 2) there is no significant difference in the profitability before and after spin-off in most sample; 3) no significant difference related to the operational efficiency.